Metabolites analysis of the marine sponge Callyspongia affinis from Kangean Island as a potential source for anticancer candidates - Moh Farid Rahman, Aulanni, Masruri, Akhmad Sabarudin, Siti Mariyah Ulfa, Edwin Setiawan (Journal of Applied Pharmaceutical Science, 2023)
This study has the objective to determine the metabolites classes contained in the hexane, EtOAc, BuOH, and aqueous fractions partitioned from the MeOH extract of the Callyspongia affinis sponge from Kangean Island, Indonesia. This study used a sponge from Kangean Island collected at 3–10 m depth as a research sample. The collected sample was then identified in the Zoology and Animal Engineering Laboratory, Sepuluh Nopember Institute of Technology, Surabaya, Indonesia. The extracts and fractions were investigated for their ability in terms of free radical scavenging, toxicity, antiproliferation, and apoptotic activity against HeLa and MCF-7 cells. The results showed that all fractions have organic nitrogen metabolites in the form of alkaloids and amide functional groups. The EtOAc and BuOH fractions contain fluorinated organic halides, while the aqueous fraction contains chlorinated organic halides. The EtOAc fraction showed the best ability as free radical 2,2-diphenyl-1-picryl-hydrazyl-hydrate scavenging with an IC50 of 27.617 μg/mL. It has the highest toxicity against Artemia salina with an LC50 of 26.652 μg/mL. The EtOAc fraction showed the best antiproliferative ability against HeLa and MCF-7 cells with IC50 values of 94.934 ± 0.700 and 97.804 ± 0.241 μg/mL, respectively. The EtOAc extract also showed the best apoptotic ability to HeLa and MCF-7 cells with IC50 values of 143.380 ± 0.010 and 131.646 ± 0.011 μg/mL, followed by MeOH extract and hexane fractions.
Keywords: Marine sponges, Ca